(untitled) (Boletín Semillero de Investigación en Familia, 2024)
Introduction: In contexts of war, care is an element that is transmitted in different ways with the objective of achieving the survival of the populations. Thus, young people are forced to develop forced to develop early in a framework of armed conflict. Objective: To describe the social practices of care for the survival of young people, between 2000 and 2010, based on the life stories of survivors in Villavicencio, Meta. Materials and methods: Qualitative research with narrative approach. The sample was a non-probabilistic snowball sample. Through the semi- structured interview, data was collected for the construction of the 10 life stories. Results: Three markers were constructed, the first one covering the context of the war; the second one evidencing significant events since childhood, and the third one, the transitions and youth agencies. Conclusions: The armed conflict in Villavicencio left deep emotional, social and economic scars on the population, but the experiences of care from the family to the community and to the processes of youth adaptation played a crucial role in individual resilience and community resilience, fostering personal development and the ability to cope with adverse contexts.